Measurement of the Underground Economy in Nepal: A Currency Demand Approach - Raut, Nirmal Kumar; Chalise, Namuna; Thapa, Puja (Economic Journal of Development Issues, 2016)
There have been rising concerns on growing magnitude of Underground Economy in most of the economies irrespective of their state of development. The problem is more apparent in developing economies where legal and institutional arrangements are relatively weaker. This study attempts to estimate empirically the size of Underground Economy in Nepal. We use an indirect method of customized version of Currency Demand Method to measure the same and find that its coverage has been increasing throughout in the last two decades with the most alarming increment in the last two fiscal years 2011and 2012. We attribute these increments particularly to the 1996-2006 armed conflict; the increasing cases of economic and financial crimes; and a large informal sector.Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 105-127